"Even a broken clock is right twice a day": The case of the Zimbardo Time Perspective Inventory. (January 2022) - McKay, Michael T.; Worrell, Frank C.; Perry, John L.; Chishima, Yuta; Zivkovic, Urška; Mello, Zena R.; Cole, Jon C.
Abstract: The number of ways in which Zimbardo Time Perspective Inventory (ZTPI) scores are operationalized has increased, and scores have begun to be used in clinical settings. A recent systematic review outlined how one operationalization, the deviation from a balanced time perspective (DBTP), was significantly associated with a range of outcomes. The review called for further investigation into the DBTP approach. Subsequently, a revised DBTP metric, the DBTP-R has been suggested. Using data from British, American, Japanese, and Slovenian samples, we asked several questions in the current study. First, we examined the structural validity of ZTPI scores using both traditional and auto-regressive approaches to see if context affects scoring. Consistent with the extant literature, results revealed serious problems with overall model fit for ZTPI scores. Then, we investigated the relationship between the DBTP and DBTP-R operationalizations of ZTPI scores and scores on a range of criterion variables. Although, broadly speaking, a DBTP score was significantly related to a range of other measures (adjusted for age and sex), results varied by sample and by outcome. DBTP-R models explained slightly more variance than DBTP models, and standardized beta values suggested that DBTP-R scores relate to criterion variables slightly more strongly than DBTP scores. Highlights: ZTPI scores were subject to both IC-CFA and Autoregressive-CFA. Fit was suboptimal for both approaches in four different samples. Scores were computed for Deviation from a balanced time perspective(-r). DBTP-r explained a little more variance than the original DBTP.